2017
DOI: 10.1159/000468924
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of the Three-Dimensional Flexible Endoscope in Endoscopic Submucosal Dissection: An ex vivo Animal Study

Abstract: Background/Aim: Clinical application of 3-dimensional (3D) technology for flexible endoscopes has not been reported. We developed a 3D flexible endoscope and conducted a feasibility study of endoscopic submucosal dissection (ESD) in porcine stomach. Methods: Four endoscopists used a 3D flexible endoscope to perform a total of 8 ESD procedures on resected porcine stomachs. We assessed the en bloc resection rate, perforation rate, and mechanical issues that arise during ESD. A visual analog scale (0, 2D superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Use of this 3-D flexible endoscopy system for performance of ESD has been reported in an ex vivo animal study, demonstrating excellent rating in depth perception and sense of security from four endoscopists. 10 In the present study, we aimed to translate the use of 3-D flexible endoscopy for carrying out submucosal dissection from preclinical animal study to clinical application of ESD in esophagus, stomach and colorectum.…”
Section: Introductionmentioning
confidence: 99%
“…Use of this 3-D flexible endoscopy system for performance of ESD has been reported in an ex vivo animal study, demonstrating excellent rating in depth perception and sense of security from four endoscopists. 10 In the present study, we aimed to translate the use of 3-D flexible endoscopy for carrying out submucosal dissection from preclinical animal study to clinical application of ESD in esophagus, stomach and colorectum.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic submucosal dissection is widely adopted as an advanced endoluminal procedure to allow en bloc resection of superficial gastrointestinal neoplasia, but is still technically challenging when using conventional endoscopes that rely solely on 2‐D information, and thus lack depth appreciation . In this regard, an ex vivo study explored the feasibility of stereovision view using a 3‐D flexible endoscope in the simulated setting of ESD . This pilot study showed that endoscopists with experience of 30 or more gastric ESD in clinical practice carried out five or more porcine gastric ESD procedures, and were then able to complete all of the procedures without any mechanical problems or perforation.…”
mentioning
confidence: 99%
“…This pilot study showed that endoscopists with experience of 30 or more gastric ESD in clinical practice carried out five or more porcine gastric ESD procedures, and were then able to complete all of the procedures without any mechanical problems or perforation. Moreover, ratings of depth perception and stability were recorded on a 100‐mm visual analog scale, and all of the participants reported a greater sense of security under 3‐D than 2‐D visualization . In the first part of ‘How Do I It?’ in the current issue, Chiu et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations